Braille Code Trainer - Syahrul Syahrul (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2009)
This report describes a research of braille code trainer. This system deals with braille codes. The functionof this system is to help the“tunanetra” so that capable to reading or recognizing of the various alphabeticalcharacters based on several of shafts by means of encoding to form a character.Both hardware and software development have been conducted. The hardware consists of a personalcomputer, a microcontroller, and some of DC gear motors. The DC gear motor is designed for movingmechanical hardware of braille code. The mechanical hardware of braille code is designed based on version ofBraille Standard. The pointers of shaft’s braille code is put on board surface that have some holes whichequivalent to braille code. The motor will push or pop on several shafts to form a braille code equivalent. Theseshafts make a contour on board surface that can be interpreted by tunanetra as alphabetical character or aspecial character. One of switches in keyboard that pressed by an instructor or a teacher through a personalcomputer make a movement of several shafts by means of a specific software.The instrument test results show that the system is capable to controlling DC gear motors for overallrepresentation of braille characters that hoped by an instructur or a teacher.Keywords: braille code, DC gear motor, microcontroller/computer, tunanetra